KEBIJAKAN MERDEKA BELAJAR SEBAGAI STRATEGI PENINGKATAN MUTU PENDIDIKAN - Rizki Ananda; Wulandari Citra Wibisono; Anugrah Kisvanolla; Pris Ajeng Purwita (Jurnal Dedikasi Pendidikan, 2023)
Quality education is education that is able to carry out the process of maturing the quality of students which is developed by freeing students from ignorance and inadequacy. With quality education, generations or superior human resources will be born in all aspects of life. Many policies have been carried out by government to improve the quality of education, such as the independent learning policy. Educational institutions are no less lagging behind in improving the quality of education by continuing to improve the quality of human resources and the quality of learning. The method used in this research is descriptive qualitative method, where descriptive research in this case is research that aims to describe the independent learning policy as an effort to improve the quality of education. While the sources taken are from  scientific books that have been published with the intention of being used as reference material. The results of this study show that the implementation of the independent learning policy aims to improve the quality of eeducation through the learning policy aims to improve the quality of education through the learning process, commitment from teachers, as well as creativity and support from school principals